Empathy and attitude of university students toward students with disabilities in Jordan: A cross-sectional study - Mutaz F. ALRADAYDEH; Izzeddin A. BDAIR; Gladys Marie L. MARIBBAY (Journal of Health and Social Sciences)
Introduction: The prevalence of students with disabilities has increased in universities recently. Negative attitudes toward students with disabilities may contribute to a negative impact on them. This study was conducted to evaluate the levels of university students’ empathy and attitude toward students with disabilities. Methods: A descriptive cross-sectional design study was conducted at a public university in Jordan. The study sample was comprised of 303 participants who were conveniently selected. Self-reported questionnaires were used to collect data, including demographic characteristics. Empathy was measured using the Basic Empathy Scale (BES). The attitude was measured using the attitude towards disabled person scale (ATDP). Results: The mean age of participants was 20.8 years (SD±1.56). Approximately half of the students were females, enrolled in scientific faculties, and in their fourth academic year. Two-thirds of students have no relatives with any mental or physical disabilities. The students showed a high level of empathy and no significant differences in empathy total scores about students’ demographics. The mean total score for ATDP was 62.99 out of 120 (SD±13.49). Female students had higher scores of ATDP than male students (M=65.48 ±13.9). Students in humanistic faculties had higher scores of ATDP than students in scientific faculties (M=64.8 ±14.1). The level of empathy among university students was negatively correlated with the total score of ATDP (r = -.197, p≤ .001). Discussion: The findings suggest that exposure to students with disabilities' culture may promote positive attitudes and better cultural understanding toward them. Actions are urgently needed to empower students with disabilities and make them feel more accepted and productive in academic institutions.